Quick Takes: Magic Moments. Issue 3 (March 2016) - Creo, Robert A.
Abstract : Editor's note: Alternatives columnist Bob Creo, a Pittsburgh arbitrator and mediator, has been revisiting his catalog of CPR Institute website columns, originated a decade ago, in a Back to Basics series that he has subtitled "Human Problems, Human Solutions." These updated and expanded columns are in print for the first time, building on new concepts and knowledge. He has revisited a wide spectrum of mediation room behaviors and practices. This month's column combines two of those early efforts .